New statin use and left ventricular structure: Estimating long‐term associations in the Multi‐Ethnic Study of Atherosclerosis (MESA). Issue 6 (30th January 2018) - Strand, Lauren N.; Young, Rebekah L.; Bertoni, Alain G.; Bluemke, David A.; Burke, Gregory L.; Lima, Joao A.; Sotoodehnia, Nona; Psaty, Bruce M.; McClelland, Robyn L.; Heckbert, Susan R.; Delaney, Joseph A.
Abstract: Purpose: Only small and short‐term studies have evaluated statins in relation to changes in heart structure. We estimated the association between new statin use and 10‐year remodeling of the left ventricle. Methods: The Multi‐Ethnic Study of Atherosclerosis collected data on statin use over approximately 10 years, conducting cardiac magnetic resonance (CMR) imaging at baseline and the 10‐year exam. Participants were free of baseline cardiovascular disease, and we excluded users of statins at baseline. Statin initiation was defined as a report of current use at any of the 4 subsequent exams. Primary outcomes were the change in left ventricular mass index (LVMI; % predicted by height, weight, and sex) and mass‐to‐volume ratio. Associations were estimated in a propensity score‐matched analysis. Results: A total of 3113 participants (53% female; 40% European‐American, 25% African‐American, 22% Hispanic‐American, and 13% Chinese‐American) were eligible; 2431 returned for follow‐up CMR imaging after a median of 9.4 years. Statin therapy (moderate dose, 76%) was started by 36% of participants (N = 872). We excluded 42 participants with incident myocardial infarction. Compared with nonuse, statin use was associated with less 10‐year progression in LVMI (−2.35 percentage points; 95% CI, −4.24 to −0.47; P  = .01) and mass‐to‐volume ratio (−0.03 absolute difference; 95% CI, −0.07 to −0.00; P  = .02); effects were small in magnitude. A dose response was observed: Higher statin dose was associated with less LVMI progression. Conclusions: In contrast to previous small studies, we found very modest associations between statin use and indices of left ventricular remodeling over 10 years in this prospective study of a diverse cohort.